AN EPISTEMOLOGICAL REVIEW OF 150 RESEARCH IN LAST THREE YEARS (2018-2020) - Amelia Idha; Emi Elma; Gita Khoirunisa; Berkat Christin; Givens Rindu; Ifan Iskandar; Ramadan Fitriani (Journal of English for Academic and Specific Purposes (JEASP), 2022)
Epistemology is concerned with possibilities, nature, and limitations of knowledge of study which focuses on what is known to be true. This study aims are to describe the development of research method epistemologically in last three years (2018-2020). So, this study will explore the epistemological basis for 150 research studies. This study will review and analyzed epistemology and include the 'theory of truth' within the range of research on English Language Education program in the last three years period from 2018–2020. The researcher used a qualitative approach in which the form of data is 150 research articles. The data source will be the 150 research that comes from English Language Education Program. The data will be analyzed by using non-statically data analysis since it is non-numerical data. From the analysis, it found that the most use methodology will be qualitative approach of descriptive qualitative. The qualitative method is already in accurate direction by selecting the social context problem, observing it, and finally resulting in theoretical analysis. Next, the quantitative method, the main problem in quantitative analysis is usually 'phenomena' that require a systematic investigation where the researcher needs to formulate a set of hypotheses.